Impact of Radio Fingerprints Processing on Localization Accuracy of Fingerprinting Algorithms - Machaj, J.; Brida, P. (Elektronika ir Elektrotechnika, 2012)
In the paper impact of different processing of measured RSS data on localization accuracy is investigated using simulations. In simulations four different fingerprinting localization algorithms developed for use with Wi-Fi were used. Used fingerprinting algorithms are described in detail. Model created in Matlab environment used for simulations is also described. Achieved simulation results shown that different processing of measured RSS data has impact on localization accuracy and can improve performance of rank based fingerprinting algorithm. Ill. 3, bibl. 6, tabl. 1 (in English; abstracts in English and Lithuanian). DOI: http://dx.doi.org/10.5755/j01.eee.123.7.2391